Reactive Oxygen Species-Based Biomaterials for Regenerative Medicine and Tissue Engineering Applications - Shafiq, Muhammad; Chen, Yujie; Hashim, Rashida; He, Chuanglong; Mo, Xiumei; Zhou, Xiaojun (Frontiers in Bioengineering and Biotechnology, 2021)
Reactive oxygen species (ROS), acting as essential mediators in biological system, play important roles in the physiologic and pathologic processes, including cellular signal transductions and cell homeostasis interference. Aberrant expression of ROS in tissue microenvironment can be caused by the internal/external stimuli and tissue injury, which may leads to an elevated level of oxidative stress, inflammatory response, and cellular damage as well as disruption in the tissue repair process. To prevent the formation of excess ROS around the injury site, advanced biomaterials can be remodeled or instructed to release their payloads in an injury microenvironment-responsive fashion to regulate the elevated levels of the ROS, which may also help downregulate the oxidative stress and promote tissue regeneration. A multitude of scaffolds and bioactive cues have been reported to promote the regeneration of damaged tissues based on the scavenging of free radicals and reactive species that confer high protection to the cellular activity and tissue function. In this review, we outline the underlying mechanism of ROS generation in the tissue microenvironment and present a comprehensive review of ROS-scavenging biomaterials for regenerative medicine and tissue engineering applications, including soft tissues regeneration, bone and cartilage repair as well as wound healing. Additionally, we highlight the strategies for the regulation of ROS by scaffold design and processing technology. Taken together, developing ROS-based biomaterials may not only help develop advanced platforms for improving injury microenvironment but also accelerate tissue regeneration.